(untitled) (World Bulletin of Public Health, 2024)
Thyroid hormones (thyroid hormones) are necessary for the normal functioning of the kidneys, which, in turn, serve not only as an organ for the metabolism and excretion of thyroid hormones, but also as a target for the action of some thyroid hormones. Hypothyroidism and hyperthyroidism are associated with clinically significant changes in renal function. Hypothyroidism is accompanied by a decrease in glomerular filtration rate (GFT), a change in the kidneys’ ability to remove water from the body.